Wordk, word that works - De la Ossa, Dora Piñeres; García, Javier Hernández; Mendoza, Estella Simancas (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
Palobra, palabra que obra, is a scientific journal in the area of social sciences, humanism and education, addressed to professionals, academics and public in general. It is published by the Faculty of social sciences and education from the University of Cartagena, Colombia, whose mission and relevance is strengthening related to the research process, it contributes to the popularization of knowledge on issues such as the construction of the local and regional socio-cultural, the structures of power in contexts such as: social groups, state, social intervention, social work, university and social transformations, family, gender, coexistence, social and human development, inclusion and exclusion-partner policy, processes and actors in the construction of public and private, imaginary, representations and discourses, territory and population in the Caribbean region, poverty, science and technology, society and innovation, education, communication and culture, in the local, regional, national and international contexts. Index-linked in C category, bibliographical National index Publidex - Colciencias and in the Regional System of Information in Line for Scientific Magazines of Latin America, the Caribbean, Spain and Portugal-Latindex. Currently, it is engaged in the processes of internationalization and integration to systems information and in expectation of its revaluation in the Network of scientific Magazines of Latin America, the Caribbean, Spain and Portugal (Redalyc). It does part of the agreement of collaboration RHELLA for the achievement of publishing joint activities.